2017
DOI: 10.1016/j.jcrs.2016.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biometry and intraocular lens power calculation performed by a new optical biometry device and a reference biometer

Abstract: The 2 devices were comparable with regard to mean IOL power, mean AL, K, and ACD measurements. However, the wide range of differences between the devices suggests they should not be used interchangeably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…Thirdly, we did not compare biometric parameters with other standard optical biometers, ie, IOL Master or Lenstar LS 900. Since sufficient evidence comparing between Pentacam AXL and IOL Master was retrieved, 8 , 10 , 11 , 18 , 21 , 22 it makes indirect comparisons among various devices possible. Corneal curvatures and axial length measured by Pentacam AXL seemed to have good agreement with those measured by IOL Master.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we did not compare biometric parameters with other standard optical biometers, ie, IOL Master or Lenstar LS 900. Since sufficient evidence comparing between Pentacam AXL and IOL Master was retrieved, 8 , 10 , 11 , 18 , 21 , 22 it makes indirect comparisons among various devices possible. Corneal curvatures and axial length measured by Pentacam AXL seemed to have good agreement with those measured by IOL Master.…”
Section: Discussionmentioning
confidence: 99%
“…New surgical techniques in conjunction with technological advances have improved the accuracy of biometry data and intraocular lens calculations. 1,2 A number of devices have proven to be reliable in calculating pre-cataract surgery measurements, including low-coherence reflectometry (Lenstar LS 900, Haag-Streit AG), Scheimpflung camera-based devices (Galilei G6, Ziemer Ophthalmic Systems AG; Pentacam, Oculus, Wetzlar, Germany) [3][4][5] and partial coherence interferometry (IOLMaster 500 and 700, Zeiss, Oberkochen, Germany). 6 The IOLMaster device is currently the most widely used device for biometric measurements.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies comparing these new devices to the ''gold standard'' optical biometer, the IOL Master 500 [7][8][9]. Recent study retrospectively compared the Galilei G6 with the IOL Master 500.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study retrospectively compared the Galilei G6 with the IOL Master 500. The devices provided similar mean IOL power, axial length (AL), keratometric and anterior chamber depth (ACD) measurements, but the authors suggested they should not be used interchangeably for biometric measurements and IOL power calculations [7]. Studies comparing the Pentacam AXL to other optical biometers found inconsistent results.…”
Section: Introductionmentioning
confidence: 99%